Mortality and hospital morbidity of working-age blind - Crewe, Julie; Morlet, Nigel; Morgan, W.; Spilsbury, Katrina; Mukhtar, Syed Aqif; Clark, Antony; Semmens, James (B M J Group, 2013)
Aim: Determine whether blindness in people aged 18–65 years was associated with increased rates of mortality, hospitalisation and length of stay. Methods: A retrospective matched cohort study of legally blind people and normally sighted controls, aged 18–65 years, comparing mortality rates and hospital morbidity records. Results: Together, 419 blind and 419 controls accumulated 12 258 hospital separations over the 11-year study period. The blind had an age-specific mortality rate seven times greater (12/1000 person years) than the general population (1.8/1000 person years) (p<0.001). Blindness was recorded as a comorbid condition for 76 (22%) blind individuals, on just 255 (2.3%) hospital separation records. Psychiatric, mental or behavioural conditions were the most frequently recorded diagnoses, after dialysis and endocrine conditions. After adjusting for comorbidities, the blind cohort had 1.5 times more hospital separations (p=0.007, 95% CI 1.1 to 2.0) and 2.2 times more bed days (p=0.016, 95% CI 1.4 to 4.1) compared with the control cohort. Conclusions: Recognition and acknowledgement of in-patients’ blind status may assist in understanding the frequent and extended health service utilisation rates. Encouraging and promoting the uptake and access to rehabilitation support services would be measures that may reduce the health service burden of blindness, the incidence of depression and other mental health problems.